Comparative Effects of Quinoa, Buckwheat, Bulgur, and Rice on Cardiometabolic Health in Adults with Overweight or Obesity: A Randomized Controlled Study - Yesim Oztekin; Buket Gonen-Colak; Selin Tekin; Incilay Lay; Tomris Erbas; Selcuk Dagdelen; Zehra Buyuktuncer (Metabolites, 2026)
Background/Objectives: The study aimed to assess cardiometabolic effects of two pseudocereals, quinoa and buckwheat, comparing them to the effects of rice and bulgur in adults with overweight or obesity. Methods: This study was conducted on 148 adults with overweight and obesity, aged between 25 and 45 years, consuming 40 g/d quinoa, buckwheat, rice, or bulgur for 4 weeks. Anthropometrical measurements were taken, and dietary intake was assessed; blood pressure and biochemical parameters were examined. Incremental areas under the curve (iAUC) for glucose and insulin were calculated. Subgroup analyses were conducted considering sex. Results: The changes in biochemical and anthropometrical measurements did not differ significantly between groups. However, within-group analysis showed significant changes in many parameters. Among anthropometrical measurements, fat mass declined significantly within quinoa and buckwheat groups (p < 0.05). Blood pressure decreased significantly in the buckwheat group, mainly in women. Fasting glucose decreased significantly only in men in the quinoa group. An increase in iAUC glucose within the bulgur group but a significant decrease in iAUC insulin among men within the buckwheat group was recorded. Total cholesterol (Total-C) significantly decreased in men but increased in women following quinoa consumption. On the other hand, a decrease was reported in high-density lipoprotein cholesterol (HDL-C) in women following quinoa and buckwheat consumption (p < 0.05). Conclusions: Compared with the baseline, the most pronounced changes were observed in blood pressure, lipid profile, and body fat mass, suggesting a potential cardiometabolic benefit of quinoa and buckwheat. However, sex-specific cardiometabolic differences may occur following the consumption of pseudocereal or cereal. Further studies are needed for more robust results.